IntentRouter-QAC: Distilling LLM-Derived Intent Signals into Small Language Models for Context-Aware Autosuggest and Search Entry Routing - Haowei Tu; Yinchen Shi; Sophia Chen (University of Science and Computer Technology, 2026)
Search boxes increasingly function as routing interfaces: a partial query may require a completion, immediate submission, a context-sensitive suggestion, or a fallback action. This paper evaluates IntentRouter-QAC as a lightweight lexical routing framework and tests product retrieval independently. Five mutually exclusive operational outcomes are derived within the 20,000-row AmazonQAC test file and evaluated with a strict session-disjoint temporal split; product-query provenance is not used as a route class. Across five seeds, the combined word/character TF-IDF router reached 0.473 mean accuracy (SD 0.031) and 0.330 mean macro-F1 (SD 0.018), indicating uneven performance across routes. On the 951-row temporal test set, context-nearest completion achieved 0.033 Success@10 and 0.025 MRR@10, compared with 0.029 and 0.023 for confidence-gated routing. The paired MRR@10 difference was 0.002 (95% CI -0.007 to 0.010; Holm-adjusted p = 1.000). Product retrieval on 480 WANDS queries and 42,994 products produced a different pattern: a word/character lexical hybrid reached 0.690 nDCG@10 and 0.504 Exact-MRR@10, significantly exceeding the title-only baseline on both measures. Route-aware decision-making is therefore useful as an architectural separation of entry actions, but it does not automatically improve exact autocomplete ranking over a strong session-context baseline.